Plastin 1 promotes osteoblast differentiation by regulating intracellular Ca2+. (21st April 2020) - Wang, Lianqing; Lan, Yongting; Du, Yanqin; Xiang, Xinxin; Tian, Wenxiu; Yang, Baoye; Li, Tao; Zhai, Qiaoli
Abstract: Osteoblast differentiation is a key process in bone homeostasis. Mutations in plastin 3 have been reported to be responsible for X-linked osteoporosis. Plastin 3 and plastin 2 act synergistically to regulate osteoblast differentiation. However, the bone-related function of plastin 1, another family member of plastins, has not been assessed. In this study, we addressed the functional importance of plastin 1 in osteoblasts. We characterized the expression patterns of plastin 1 during osteoblast differentiation and revealed its important role in this process. In both HEK 293T and hFOB1.19 cells, plastin 1 was demonstrated to regulate intracellular Ca 2+ . Accordingly, we revealed that higher Ca 2+ concentration promotes osteoblast differentiation. Finally, we found that plastin 1 may play a compensatory role in osteoporosis patients with plastin 3 deficiency. Together, our results indicate that plastin 1 promotes osteoblast differentiation by regulating intracellular Ca 2+ . Our work sheds new light on the role played by plastins in bone homeostasis.